Twin suppression by atomic scale engineering of precipitate-matrix interfaces. (15th April 2023) - Jin, X.Z.; Wang, C.Y.; Milenkovic, S.; Sabirov, I.; Beyerlein, I.J.; Pérez-Prado, M.T.
Abstract: This work aims to investigate the influence of solute segregation at particle-matrix interfaces on the twin activity of aged Mg alloys. With that purpose a binary Mg-8Al alloy (wt%) and two ternary Mg-8Al-1 Zn and Mg-8Al-1Ag alloys (wt%) were first homogenized and then aged in order to obtain comparable precipitate distributions. Particle-matrix interfaces in the binary alloy were observed to be clean, while Zn and Ag atomic segregation was clearly present at the interfaces of the ternary alloys. Room temperature micropillar compression tests were carried out in grains with favorable orientations for tensile twinning in the homogenized and the aged conditions for the three materials under investigation. The activation of twinning and slip was then characterized by electron microscopy. This study shows that while in the binary alloy precipitation did not lead to any major changes in the twinning activity and, in particular, it did not prevent the formation of thick twin lamellae encompassing the entire width of the tested micropillars, a drastic reduction of the twin activity took place in the aged ternary alloys. In the latter, straining led to the formation of narrow twin lamellae belonging to a single variant, and occasionally arrested at the interior of the micropillars. We propose that the drastic reduction of the twin volume fraction in the aged ternary alloys may be attributed to the decrease of the particle-matrix interface energy due to Zn and Ag segregation, which would hinder re-nucleation at such interfaces, thus suppressing twin propagation. Graphical abstract: Image, graphical abstract